2015
DOI: 10.1002/14651858.cd010480.pub2
|View full text |Cite
|
Sign up to set email alerts
|

HMG CoA reductase inhibitors (statins) for preventing acute kidney injury after surgical procedures requiring cardiac bypass

Abstract: HMG CoA reductase inhibitors (statins) for preventing acute kidney injury after surgical procedures requiring cardiac bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 107 publications
0
26
0
2
Order By: Relevance
“…A recent meta-analysis by Wang et al, including 11 studies, showed that preoperative statin treatment reduced the incidence of post-operative AKI by 13% (8). However, the results of this meta-analysis should be interpreted with caution as the presence of supporting evidence of attenuation of AKI after cardiac surgery with preoperative statin treatment has been challenged (9). Prior studies examining specifically shortterm initiation of statins have also showed contradictory results.…”
mentioning
confidence: 86%
“…A recent meta-analysis by Wang et al, including 11 studies, showed that preoperative statin treatment reduced the incidence of post-operative AKI by 13% (8). However, the results of this meta-analysis should be interpreted with caution as the presence of supporting evidence of attenuation of AKI after cardiac surgery with preoperative statin treatment has been challenged (9). Prior studies examining specifically shortterm initiation of statins have also showed contradictory results.…”
mentioning
confidence: 86%
“…sogar eine erhöhte AKI-Rate bei Patienten, die perioperativ mit Statinen behandelt wurden, gezeigt werden konnte [7,34,44,85]. …”
Section: Kardiochirurgische Patientenunclassified
“…The remaining four trials observed no difference in renal outcome between those receiving short-term pre-operative statins and given placebo [58][59][60][61][62][63]. Much of this is summarised in a recent metaanalysis in the Cochrane database of the impact of statins on the occurrence of AKI after procedures requiring cardiac bypass by Lewicki and colleagues [64]. The conclusion was the available data do not suggest that pre-operative statin use is associated with decreased incidence of AKI in adults in such circumstances, nor do they indicate an increased incidence of AKI.…”
Section: 2mentioning
confidence: 99%